UJI PEMBERIAN PEG 6000 TERHADAP MORFOLOGI BENIH KARET (Hevea brassiliensis, Muell-Arg.) TANPA CANGKANG SETELAH PENYIMPANAN - Muhammad Husni; Charloq Charloq; B Siagian (Jurnal Agroekoteknologi, 2014)
ABSTRACTGiving test of PEG 6000 to morphology of rubber seeds (Hevea brassiliensis, Muell-Arg.) shellesafter storage. Rubber seeds are recalcitrant seeds have a very high water content, low storability, sorapid had deterioration, and therefore required special treatment on the storage period to maintainseed viability. Using PEG 6000 increased storage recalcitrant seeds because it has the potential tolimit cell osmoticum changes in water content and oxygen on seed. The purpose of this study to getthe right PEG 6000 concentration to improve seed storability. The research was conducted inJanuary and March 2012 at the Seed Technology Laboratory, Agricultural Faculty, Sumatera UtaraUniversity, Medan – Indonesia. Randomly complete design was applied with four treatments andfour replications, i.e: PEG 6000 ; 0, 150, 300, 450 (gr/l aquadest). Parameters observed germinateseeds in storage and recapitulation germinate seeds ability after storage. The results showed thatPEG 6000 was significantly on germinated seeds in storage but not siqnificant effect on seedgermination after storage and best result was achieved at PEG 300 gr/l aquades, germinated seedsin storage was 0,33% and recapitulation germinate seeds ability after storage was 80,09%.Key words: PEG 6000, rubber seed, seed storage